Tubos atomizadores de titânio em espectrometria de absorção atômica com forno tubular na chama e aerossol térmico (TS-FF-AAS) para a determinação de cobre em materiais biológicos - Gomes, Marcos da Silva (Universidade Federal de São Carlos, 2009)
In this work it was used Ti atomizers tubes employing TS-FF-AAS system to improve the analytical performance of FAAS. The TS-FF-AAS was applied for Cu determination in food and biological samples. The Ti tubes were used as an alternative of the Ni tubes. It was evaluated different arrangements of Ti tubes, as well as tubes combining Ni and Ti (Ni/Ti) inserting Ti tube inside Ni tubes. A 24 factorial design was performed in order to evaluate the influence of several variables in the system. The best results were achieved using a 300 L sample loop, 5 mm tube height, 0.4 mL min-1 carrier flow rate, and 70 mm Ti tube length. Tube length was the most important variable, presenting a positive effect of 30%. This high sensitivity is related to the formation of TiO2 (confirmed by microanalysis and X-ray difractometry) inside the Ti tube (gain of 45% mass in comparisson of inicial mass), improving the Cu atomization through the oxide via. The detection limit obtained was 2 µg L-1 . Gaseous phase temperatures of Ni, Ti, and Ni/Ti tubes were estimate using a Sn 150 mg L-1 solution in order to explain differences in sensitivity. The estimated temperatures for the tubes (Ni, Ti and Ni/Ti) were in the same magnitude, suggesting that the temperature in the gaseous phase is not the reason for high sensitivity using Ni/Ti tubes. Cu 500 µg L-1 signal was measured in the presence of Ca, K, Mg and Na using a 24 factorial design. According to the probability graphic a 10 % increase in the Cu signal was observed only when Mg was present and K presence decrease the Cu signal. The behaviors of the Ni and Ni/Ti atomizers tubes were similar in the concomitants presence. The method accuracy was confirmed using certified references materials (CRM’s). The samples were digested by microwave-assistence and the recoveries values ranged from 91 to 107%. The unpared t test did not show statistic difference between certified and found values, into the confidence level of 95%.
Use of titanium atomizers tubes in thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS)
Keywords: Espectrometria; Spectrometry; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE